Supplementation alimentaire des boeufs de labour du systeme agropastoral du mil a Dalonguebougou: effet compare de deux regimes de supplementation en fanes de niebe - Traoré, A.; Soumare, S. (CIPEA, 1985)
Examines the effects of cowpea haulm supplementation on the maintenance and work output of draft animals in the millet agropastoral system of central Mali.